M1-D FDTD methods for mobile interactive teaching and learning of wave propagation in transmission lines - Tan, Eng Leong (2020)
This article presents the multiple 1D finite-difference time-domain (M1-D FDTD) methods for mobile interactive teaching and learning of wave propagation in transmission lines (TLs). Both the M1-D explicit FDTD method and the unconditionally stable M1-D fundamental alternating direction-implicit (FADI) FDTD method are discussed. Using the M1-D FDTD methods, multiple TLs, stubs, and circuit elements can be simulated efficiently. They are readily implemented on mobile devices and applied for mobile interactive teaching and learning of TL topics, including wave reflections from stubs, standing waves, and impedance matching. These topics can be elucidated clearly through interactive visualizations on mobile devices. Using the unconditionally stable M1-D FADI-FDTD method, the simulation may be "fast-forwarded" with enhanced efficiency by using a time-step size larger than the stability constraint. Student surveys and tests demonstrated the effectiveness of the method.